A study of service quality performance made by Opensoft Technologies Sdn Bhd / Norshafini Md Hussain - Md Hussain, Norshafini (2009)
This research was conducted for the purposed of “A Study of Service Quality Performance Made by Opensoft Technologies Sdn. Bhd.” The main purpose of this research was to examine overall customer satisfaction toward the service and the performance of the outsourced job taken by Opensoft Technologies Sdn. Bhd. based on the SERVQUAL dimensions. In this research, the researcher focused on the case from the outsource job taken by Opensoft Technologies Sdn. Bhd. from Jabatan Pertanian, Kementerian Pertanian dan Asas Tani,Putrajaya. The research is conducted using primary and secondary data. The data being collected through interview and observation as primary data while from secondary data is gathered information through journal, article, and textbook and also through internet. The conclusion of the research was the outcome from the gap identification that was compared between the theory and company practices. Based on the finding, some recommendations have been suggested in order to help this company improve their quality of services and at the same time, enhance customer satisfaction.